2004
DOI: 10.1210/jc.2003-031388
|View full text |Cite
|
Sign up to set email alerts
|

Perilipin Expression in Human Adipose Tissue Is Elevated with Obesity

Abstract: The perilipins are highly phosphorylated adipocyte proteins that are localized at the surface of the lipid droplet. With activation by protein kinase A, perilipins translocate away from the lipid droplet and allow hormone-sensitive lipase to hydrolyze the adipocyte triglycerides to release nonesterified fatty acids (NEFA). Because of the potential importance of adipocyte lipolysis to obesity and insulin resistance, we measured perilipin protein and mRNA levels in nondiabetic subjects with varying degrees of in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
90
0
6

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(102 citation statements)
references
References 40 publications
6
90
0
6
Order By: Relevance
“…Several of these genes are known to play a role in lipid transport or lipid droplet function and leptin expression has repeatedly been shown to tightly correlate with the amount of lipid stores Maffei et al, 1995). There are also reports of a correlation between adiposity and expression of Rbp4 (Kelly et al, 2010;Lee et al, 2007) and perilipin, a protein that is localized to the surface of the lipid droplets in adipocytes (Kern et al, 2004). These data further suggest that distinct transcriptional mechanisms may regulate genes that control adipocyte differentiation versus those associated with lipid accumulation and that these processes are regulated independently during development in vivo.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several of these genes are known to play a role in lipid transport or lipid droplet function and leptin expression has repeatedly been shown to tightly correlate with the amount of lipid stores Maffei et al, 1995). There are also reports of a correlation between adiposity and expression of Rbp4 (Kelly et al, 2010;Lee et al, 2007) and perilipin, a protein that is localized to the surface of the lipid droplets in adipocytes (Kern et al, 2004). These data further suggest that distinct transcriptional mechanisms may regulate genes that control adipocyte differentiation versus those associated with lipid accumulation and that these processes are regulated independently during development in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, the genes in cluster 11 are induced later in development, concomitant with appearance of lipidfilled unilocular adipocytes (Fig. 1B) and include leptin, retinol binding protein (Rbp4) and fatty acid synthase (Fasn), all of which are expressed in mature adipocytes (Kern et al, 2004;Lee et al, 2007;Menendez et al, 2009). Cluster 11 also contains transcription factors that have been implicated in adipogenesis, such as Ebf1 (Jimenez et al, 2007), which, based on these data, could have additional roles in regulating or responding to lipid accumulation in vivo.…”
Section: Research Articlementioning
confidence: 99%
“…Interestingly, knockdown of CIDEA in human adipocytes increases both lipolysis and the expression of TNF-α, a cytokine implicated in the development of obesity-associated insulin resistance. One study reported that PLIN1 mRNA and protein expression was reduced in adipocytes in morbidly obese men and women (93), although another laboratory found that PLIN1 expression increases with obesity (94). Other investigators have linked levels of PLIN1 expression in adipocytes to rates of constitutive lipolysis (95), an observation that is consistent with a reduction of PLIN1 with obesity.…”
Section: Role Of Cide/plin1 In Obese Animals and Humansmentioning
confidence: 96%
“…PLIN expression is increased in the adipose tissue of obese subjects. 98 One intronic PLIN SNP is associated with mRNA levels and lipolysis, rs891460 A/G in intron 6. 99 Additional intronic SNPs in the PLIN gene in women have been reported to be associated with obesity phenotypes.…”
Section: Pathways Controlling Lipid Storage In Adipocytesmentioning
confidence: 99%